Usage of Antifungal Drugs for Therapy of Genital Candida Infections, Purchased as Over-the-Counter Products or by Prescription: 1. Analyses of a Unique Database - Per-Anders Mårdh; Jolanta Wågström; Maria Landgren; Jan Holmén (Hindawi Limited, 2004)
Objectives: To present sales figures of antifungal drugs for treatment of genital Candida infections in females, which had been purchased in the Swedish county of Skåne (with approximately 1.2 million inhabitants) during the 1990s. To study the relative proportions of the drugs sold by prescription and as over-the-counter (OTC) products.